Integrasi Pendidikan Karakter dengan Deep Learning sebagai Fondasi Peningkatan Mutu Pendidikan di SMA Negeri 2 Kota Tangerang Selatan - Hidayati, Syafaatul; Hidayat, Ahmad; Rahman, Arip (Universitas Pamulang, 2026)
Character education plays an essential role in shaping students’ personalities by fostering moral values, ethics, and social responsibility. Nevertheless, its implementation in schools is often still conceptual and has not been fully integrated into technology-based learning. This article aims to describe the development of an integrated character education model through a Deep Learning approach as an innovative learning strategy at SMA Negeri 2 South Tangerang City. This approach combines the use of artificial intelligence technology with a deep learning approach implemented through project-based learning oriented toward solving real-world problems. The program activities include teacher training, classroom implementation of the learning model, and evaluation of its impact on learning quality and student behavior. It is expected that this program will produce a character education model that is responsive to the digital era, enhances the quality of the teaching and learning process, and instills values of discipline, cooperation, honesty, and responsibility in students. This model is also expected to serve as a reference and be replicated in other schools in Indonesia. Keywords: Character Education, Deep Learning, PjBL, Learning Innovation